ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT UMKM MUSLIM MENGGUNAKAN QUICK RESPONSE CODE INDONESIA STANDARD (QRIS) DI KELURAHAN PAGAR DEWA KOTA BENGKULU - Denny Riyanto; Eka Sriwahyuni; Andi Harpepen (Universitas Islam Negeri Mataram, 2024)
Bank Indonesia (BI) launched a Quick Response (QR) standard for payments through server-based electronic money applications, digital wallets, or mobile banking. Quick Response Code Indonesian Standard is a unification of various types of QR from various Payment System Service Providers (PJSP) using QR Code developed by Bank Indonesia and the Indonesian Payment System Association which aims to integrate all cashless payment methods in Indonesia. In the era of digit trends the growing number of merchants switched to non-cash payment systems. The purpose of this study is to determine the factors that influence the use of QRIS for MSMEs in the city of Bengkulu, to analyze the benefits and facilities of the interest of MSME users in the city of Bengkulu.